Cover Picture: Nanostructured Particles for Controlled Polymer Release in Enhanced Oil Recovery (Energy Technol. 9/2016). Issue 9 (31st August 2016) - Tamsilian, Yousef; S. A., Ahmad Ramazani; Shaban, Masoom; Ayatollahi, Shahab; de la Cal, Jose C.; Sheng, James J.; Tomovska, Radmila
Abstract : Smart Enhanced Oil Recovery Process using Core–Shell Nanoparticles : The cover image denotes schematically the enhanced oil recovery process by flooding using an aqueous dispersion of core–shell nanoparticles made up of protected polyacrylamide nanostructures (PPNs). Y. Tamsilian and his colleagues at Sharif University of Technology (Iran) and the Institute for Polymer Material (POLYMAT, Spain) demonstrated the synthesis of polyacrylamide nanoparticles protected with a hydrophobic polystyrene shell by using a one‐pot, two‐step inverse emulsion polymerization technique, where the polystyrene shell was created by surface polymerization. The presence of the hydrophobic shell assures the protection of active PAM chains from premature degradation in the presence of the harsh environment of the reservoir and simultaneously controls the polymer release as a rheological modifier. Additionally, the preparation provides the chains with prolonged stability.PPNs act as smart nanostructures. Once injected into the reservoir as an aqueous dispersion (point 0) with a viscosity similar to that of water, they are pumped to reach the targeted oil (point 1). The oil dissolves the polystyrene shell, allowing the release of polyacrylamide active chains to increase the viscosity of the pushing aqueous dispersion. The displacing high‐viscosity fluid is pushed forward toward the production well (point 2), and, due to the change in mobility ratios between the aqueous and oil phase, it enhances the oil recovery from the reservoirs. More details can be found in the Full Paper by Yousef Tamsilian et al. on page 1035 in Issue 9, 2016 (DOI: 10.1002/ente.201600036).